Levels of malondialdehyde-related immune reactants in a lupus prone mouse strain - Danial Yahya, M.; Chien , C. Lung; Yacob L. Pinnas (Universiti Kebangsaan Malaysia, 1996)
The levels of malondialdehyde (MDA)-specific antibodies in lupus-prone MRL/ lpr mice of different ages were compared to those against DNA. These mice elicited anti-MDA antibodies earlier and in higher levels that anti-DNA antibodies. The levels of immune complexes containing MDA adducts were also higher in these mice when compared to 3 other non-lupus strains. MDA binding to a 100 kDa serum protein was observed in 3 and 5 month old mice. Immune complexes involving anti-MDA antibodies and MDA adducts may represent an additional mechanism that contributes to disease pathogenesis in these mice.